The role of principal transformational leadership based on Lonto Leok culture Manggarai community for strengthening student character - Pieter Sahertian; Yulius Rustan Effendi (Masyarakat, Kebudayaan dan Politik, 2022)
The role of the principal is crucial to optimize the implementation of the student character strengthening program. Unfortunately, the role of the principal is experiencing obstacles because he has not found the appropriate form of role and approach to make the student character strengthening program effective. This study examines the principal's transformational leadership role based on a local cultural system. A qualitative approach is used in this study, the case study design with the subjects studied were school principals. Participants in this study include three principals, three senior teachers, one parent, and one cultural figure. Data were collected through in-depth interviews, participant observation, and documentation studies to achieve the research objectives. Data analysis employed a modified analytical analysis method. Meanwhile, the validity of the data was based on the level of credibility, transferability, dependence, and confirmability. The study results prove that the principal's transformational leadership role with a local cultural approach has a positive impact on the optimization of character strengthening programs and positive changes in students' moral behavior. The study concludes that the transformational leadership role of local culture-based principals impacts optimizing student character strengthening programs.